Research on a New Bilateral Self-locking Mechanism for an Inchworm Micro In-pipe Robot with Large Traction. (28th October 2014) - Yang, Junhong; Xue, Yong; Shang, Jiangzhong; Luo, Zirong
In this paper, we present an innovative bilaterally-controllable self-locking mechanism that can be applied to the micro in-pipe robot. The background and state of the art of the inchworm micro in-pipe robot is briefly described in the very beginning of the paper, where the main factors that influence the traction ability are also discussed. Afterwards, the micro in-pipe robots' propulsion principle based on a unidirectional self-locking mechanism is discussed. Then, several kinds of self-locking mechanisms are compared, and a new bilaterally-controllable self-locking mechanism is proposed. By implementing the self-locking mechanism, the robot's tractive force is no longer restricted by the friction force, and both two-way motion and position locking for the robot can be achieved. Finally, the traction experiment is conducted using a prototype robot with the new bilaterally-controllable self-locking mechanism. Test results show that this new self-locking mechanism can adapt itself to a diameter of >17 >20 mm and has a blocking force up to 25N, and the maximum tractive force of the in-pipe robot based on such a locking mechanism is 12N under the maximum velocity of 10mm/s.